Low‐dose aspirin desensitization in individuals with aspirin‐exacerbated respiratory disease. Issue 5 (7th March 2013) - Fruth, K.; Pogorzelski, B.; Schmidtmann, I.; Springer, J.; Fennan, N.; Fraessdorf, N.; Boessert, A.; Schaefer, D.; Gosepath, J.; Mann, W. J.
Abstract Background Nasal polyposis frequently occurs within the clinical picture of aspirin‐exacerbated respiratory disease (AERD). A derailed arachidonic acid metabolism is regarded to be part of the pathophysiology of AERD, and aspirin desensitization is the only causal therapeutic option, so far. The optimal maintenance dose of aspirin desensitization to prevent nasal polyp recurrence on the one hand and to minimize aspirin‐related side‐effects, on the other hand, is still a matter of debate. The aim of this trial was to investigate the efficacy and safety of a low‐dose aspirin desensitization protocol. Methods After sinus surgery, 70 individuals with AERD were randomly allocated to a prospective double‐blind placebo‐controlled aspirin desensitization protocol with a maintenance dose of 100 mg daily. The primary outcome was polyp relapse after 36 months. Nasal endoscopy status, quality of life, and patients' symptom score as well as aspirin‐related side‐effects were monitored. Results Due to the high dropout rate, only 31 individuals were evaluated. After 36 months, nasal polyp relapse was less frequent (P = 0.0785) and the polyposis score was lower (P = 0.0702) in the therapy group. Quality of life obviously improved (P = 0.0324), clinical complaints (P = 0.0083) were significantly reduced, and no severe aspirin‐related side‐effects were observed. Conclusion Aspirin desensitization with a maintenance dose of 100 mg daily has a positive impact on nasal polyp relapse and seems to be a safe and suitable therapy to improve clinical complaints and the quality of life of individuals with AERD.